2018
DOI: 10.1039/c7fd00155j
|View full text |Cite
|
Sign up to set email alerts
|

Atomic charges of sulfur in ionic liquids: experiments and calculations

Abstract: Experimental near edge X-ray absorption fine structure (NEXAFS) spectra, X-ray photoelectron (XP) spectra and Auger electron spectra are reported for sulfur in ionic liquids (ILs) with a range of chemical structures. These values provide experimental measures of the atomic charge in each IL and enable the evaluation of the suitability of NEXAFS spectroscopy and XPS for probing the relative atomic charge of sulfur. In addition, we use Auger electron spectroscopy to show that when XPS binding energies differ by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 74 publications
4
29
0
Order By: Relevance
“…Recently it was proposed that the BEs obtained from fitting the experimental XPS spectra for ILs correlate with the calculated atomic charges. [ 32,33 ] Figure 6 demonstrates a modest correlation between the BE approximated by the first and third terms of Equation ) (BE = V [ q i ]) and the calculated relative ΔKS BE values. The relation improves significantly by considering the effect of the electrostatic potential of neighboring atoms given by the second term in Equation ) (BE = V [ q i , q j ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was proposed that the BEs obtained from fitting the experimental XPS spectra for ILs correlate with the calculated atomic charges. [ 32,33 ] Figure 6 demonstrates a modest correlation between the BE approximated by the first and third terms of Equation ) (BE = V [ q i ]) and the calculated relative ΔKS BE values. The relation improves significantly by considering the effect of the electrostatic potential of neighboring atoms given by the second term in Equation ) (BE = V [ q i , q j ]).…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 ] Fogarty et al found such correlation for the S 1s electrons ( R 2 = 0.98) and N 1s electrons ( R 2 = 0.94) between the experimental BEs and the computed atomic charges. [ 32,33 ] Kruusma et al calculated C 1s electrons' Kohn–Sham (KS) orbital energies and used their values for fitting the experimental spectra. [ 17 ] Similarly, Reinmöller et al used the KS orbital energies to calculate the BEs for the XPS spectra.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the lack of standard procedures, different C 1s fitting models have been developed for even the most basic IL chemical structures. For example, the C 1s region of imidazolium ILs have been fitted with 2-3 component models, which broadly account for polar and non-polar regions, 32 or more complex fittings with 3+ components. 21,33 While the latter can potentially provide more information, simpler models are a conservative approach aimed at minimising over interpretation of XP spectra.…”
mentioning
confidence: 99%
“…shifts < 0.5 eV in IL XP spectra in terms of atomic charges. 32,37 Despite this, correlations between core-electron B.E.s and physicochemical properties (e.g. Kamlettaft parameters) 21,22,31 support the drive for accurate peak fittings, regardless of the physical interpretation of the data.…”
mentioning
confidence: 99%
“…Lovelock and co‐workers reported a systematic investigation of several ILs by means of NEXAFS (near‐edge X‐ray absorption fine structure) spectroscopy and XPS (X‐ray photoelectron spectroscopy) . In these experiments, the core electrons of a given atom are excited to an unoccupied molecular orbital by X‐ray radiation.…”
Section: Electronic Spectroscopymentioning
confidence: 99%